Tsunami generation and associated waves in the water column and seabed due to an asymmetric earthquake motion within an anisotropic substratum. Issue 10 (20th October 2016) - Bagheri, Amirhossein; Greenhalgh, Stewart; Khojasteh, Ali; Rahimian, Mohammad; Attarnejad, Reza
Abstract: In this paper, closed‐form integral expressions are derived to describe how surface gravity waves (tsunamis) are generated when general asymmetric ground displacement (due to earthquake rupturing), involving both horizontal and vertical components of motion, occurs at arbitrary depth within the interior of an anisotropic subsea solid beneath the ocean. In addition, we compute the resultant hydrodynamic pressure within the seawater and the elastic wavefield within the seabed at any position. The method of potential functions and an integral transform approach, accompanied by a special contour integration scheme, are adopted to handle the equations of motion and produce the numerical results. The formulation accounts for any number of possible acoustic‐gravity modes and is valid for both shallow and deep water situations as well as for any focal depth of the earthquake source. Phase and group velocity dispersion curves are developed for surface gravity (tsunami mode), acoustic‐gravity, Rayleigh, and Scholte waves. Several asymptotic cases which arise from the general analysis are discussed and compared to existing solutions. The role of effective parameters such as hypocenter location and frequency of excitation is examined and illustrated through several figures which show the propagation pattern in the vertical and horizontal directions. Attention is directed to the unexpected contribution from the horizontal ground motion. The results have important application in several fields such as tsunami hazard prediction, marine seismology, and offshore and coastal engineering. In a companion paper, we examine the effect of ocean stratification on the appearance and character of internal and surface gravity waves. Key Points: Closed‐form expressions are presented for waves in an ocean and the solid substratum generated due to a ground motion within the seabed The contribution of the horizontal ground motion in addition to the vertical motion is examined and found to be considerable Both shallow and deep sources are investigated and parameters such as seabed anisotropy and frequency of excitation are included